Insights how expert principals make difficult decisions - McLaughlin, Dionne V. (Thousand Oaks, California Corwin, 2015)
"Essential to inspiring and improving schools, principals make complex decisions on a daily basis. This invaluable resource offers extensive case studies to explore how expert principals manage crises, navigate tough choices, and support school environments. A former elementary and secondary school site administrator, the author presents a highly sensible, cohesive, and research-based approach to decision making that will greatly benefit school principals at any career stage"--Back cover.
Part 1: factors expert principals consider in decision making. Chapter 1: weighing options -- Chapter 2: recognizing and connecting to core values -- Chapter 3: considering the culture before introducing change -- Chapter 4: examining the whole picture -- Part II: making difficult decisions. Chapter 5: decisions about student consequences -- Chapter 6: decisions about faculty and staff -- Chapter 7: decisions about practices, policies, and programs -- Chapter 8: decisions that improve African American and Latino student achievement.
Includes bibliographical references (pages 143-145) and index.
Keywords: School principals -- United States; School management and organization -- United States